2022
DOI: 10.1007/s11356-022-20599-y
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus awamori attenuates ochratoxin A-induced renal and cardiac injuries in rabbits by activating the Nrf2/HO-1 signaling pathway and downregulating IL1β, TNFα, and iNOS gene expressions

Abstract: Ochratoxin A (OTA) is one of the most dangerous and that pollute agricultural products, inducing a variety of toxic effects in humans and animals. The current study explored the protective effect of different concentrations of Aspergillus awamori (A. awamori) against OTA (0.3 mg/kg diet) induced renal and cardiac damage by exploring its mechanism of action in 60 New Zealand white male rabbits. Dietary supplementation of A. awamori at the selected doses of 50, 100, and 150 mg/kg diet, respectively, for 2 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 113 publications
2
1
0
Order By: Relevance
“…[18,20]. These findings were in agreement with [21], while [22] reported that rabbits given OTA demonstrated a variety of histological changes, hyperemia in glomerular capillaries, interstitial vasculature, and clearly visible vacuolar tubular epithelial degradation. Other renal tubules also showed cystic dilatation with pressure atrophy on neighboring tubules.…”
Section: Results and Discussion Histopathological Studysupporting
confidence: 87%
“…[18,20]. These findings were in agreement with [21], while [22] reported that rabbits given OTA demonstrated a variety of histological changes, hyperemia in glomerular capillaries, interstitial vasculature, and clearly visible vacuolar tubular epithelial degradation. Other renal tubules also showed cystic dilatation with pressure atrophy on neighboring tubules.…”
Section: Results and Discussion Histopathological Studysupporting
confidence: 87%
“…The increase in (MCH) analysis is attributed to liver disease or cancer, while the decrease from the control treatment indicates anemia [15]. These results were similar to the findings of Assar et al (2022) [16] , which showed anemia as a decrease in the numbers of red blood cells and lymphopenia, and differed in an increase in WBC, MCV and MON, Results for MCH and MCHC did not agree with OTA treatment , while they were identical to CIT treatment When New Zealand rabbits were treated with a dose of 0. [18] demonstrated elevated MCV and MCH while white blood cell (WBC), hemoglobin (HB), red blood cell (RBC), Haematocrit (PCV) and MCHC) were observed to be significantly decreased in Liza ramada fish fed OTA at a dose of Its concentration is 1 mg/kg.…”
Section: Testing the Combined Effects Of The Mycotoxins Citrinin And ...supporting
confidence: 84%
“…It is commonly believed that the molecular imbalance of oxidative stress contributes to the progression and development of acute and chronic kidney diseases [19][20][21]. Administration of CP could promote a significant (p < 0.05) increase in MDA levels and a significant (p < 0.05) decrease in the antioxidant capacity as revealed by a decline in the renal…”
Section: Pv Diminished Cp-promoted Renal Oxidative Stressmentioning
confidence: 99%